Religion, faith, and spirituality influences on HIV prevention activities: A scoping review. - Vivian Vigliotti; Tamara Taggart; Mahaya Walker; Sasmita Kusmastuti; Yusuf Ransome (PLoS ONE)
Introduction Strategies to increase uptake of next-generation biomedical prevention technologies (e.g., long-acting injectable pre-exposure prophylaxis (PrEP)) can benefit from understanding associations between religion, faith, and spirituality (RFS) and current primary HIV prevention activities (e.g., condoms and oral PrEP) along with the mechanisms which underlie these associations. Methods We searched PubMed, Embase, Academic Search Premier, Web of Science, and Sociological Abstracts for empirical articles that investigated and quantified relationships between RFS and primary HIV prevention activities outlined by the United States (U.S.) Department of Health and Human Services: condom use, HIV and STI testing, number of sexual partners, injection drug use treatment, medical male circumcision, and PrEP. We included articles in English language published between 2000 and 2020. We coded and analyzed studies based on a conceptual model. We then developed summary tables to describe the relation between RFS variables and the HIV prevention activities and any underlying mechanisms. We used CiteNetExplorer to analyze citation patterns. Results We identified 2881 unique manuscripts and reviewed 29. The earliest eligible study was published in 2001, 41% were from Africa and 48% were from the U.S. RFS measures included attendance at religious services or interventions in religious settings; religious and/or spirituality scales, and measures that represent the influence of religion on behaviors. Twelve studies included multiple RFS measures. Twenty-one studies examined RFS in association with condom use, ten with HIV testing, nine with number of sexual partners, and one with PrEP. Fourteen (48%) documented a positive or protective association between all RFS factors examined and one or more HIV prevention activities. Among studies reporting a positive association, beliefs and values related to sexuality was the most frequently observed mechanism. Among studies reporting negative associations, behavioral norms, social influence, and beliefs and values related to sexuality were observed equally. Studies infrequently cited each other. Conclusion More than half of the studies in this review reported a positive/protective association between RFS and HIV prevention activities, with condom use being the most frequently studied, and all having some protective association with HIV testing behaviors. Beliefs and values related to sexuality are possible mechanisms that could underpin RFS-related HIV prevention interventions. More studies are needed on PrEP and spirituality/subjective religiosity.